2018
DOI: 10.1038/s41598-017-15564-6
|View full text |Cite
|
Sign up to set email alerts
|

Electron beam melting in the fabrication of three-dimensional mesh titanium mandibular prosthesis scaffold

Abstract: The study was designed to fulfill effective work-flow to fabricate three-dimensional mesh titanium scaffold for mandibular reconstruction. The 3D titanium mesh scaffold was designed based on a volunteer with whole mandible defect. (1) acquisition of the CT data; (2) design with computer aided design (CAD) and finite element analysis (FEA). The pore size and intervals with the best mechanic strength was also calculated using FEA. (3) fabrication of the scaffold using electron beam melting (EBM); (4) implantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Furthermore, any discrepancy would result in implant failure, a greater number of amendments and psychological stress on the patient's mind. Henceforth, to minimize disparities and conform bone contours as well as provide enhanced cosmetic output, it is imperative to make use of the concept of customized implant design [12,13]. The customized design of an implant can improve fitting accuracy significantly and reduces the operation time in contrast to standard plates.The rapidly growing health care demands owing to aging, expanding the global population, etc., emphasize the importance of innovative technologies in the medical field.…”
mentioning
confidence: 99%
“…Furthermore, any discrepancy would result in implant failure, a greater number of amendments and psychological stress on the patient's mind. Henceforth, to minimize disparities and conform bone contours as well as provide enhanced cosmetic output, it is imperative to make use of the concept of customized implant design [12,13]. The customized design of an implant can improve fitting accuracy significantly and reduces the operation time in contrast to standard plates.The rapidly growing health care demands owing to aging, expanding the global population, etc., emphasize the importance of innovative technologies in the medical field.…”
mentioning
confidence: 99%
“…This involves incorporating existing surface modification techniques to complex AM porous architectures or developing new strategies, where achieving uniform external and internal surface modification that also meets requirements for infection control whilst simultaneously promoting osteogenic differentiation is a newly‐presented challenge. [ 18,79 ] Nevertheless, promising reported strategies under development include a study by Jia et al who investigated the combination of silver nanoparticles to micro‐arc oxidized/hydrothermal treated AM Ti‐6Al‐4V scaffold with the aid of a dopamine coating, where they described achieving the three‐in‐one goal of infection prophylaxis, infection‐fighting and bone repair. [ 77,80 ] Xu et al evaluated copper incorporated SLM Ti‐6Al‐4V surfaces populated with macrophages, osteoclasts and osteoblasts, and demonstrated suppressed inflammatory response and osteoclastogenesis, meanwhile promoting bone extracellular matrix formation by osteoblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Additive manufacturing (AM) expands the possibility to fabricate complex, anatomically matched orthopedic implants. [ 17–19 ] To further increase bony integration, a number of surface modification strategies have been investigated; however, popular physical depositions have the risk of delamination (e.g., hydroxyapatite coating) and subtraction approaches might influence the mechanical and fatigue properties (e.g., sandblasting). [ 20 ] Electrochemical anodization is another appealing strategy that results in surface nano‐texturing by creating regular nanotubes on the titanium surface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the type of fibular flap that is applied in surgery plays a critical role in the success of long-term stable osseointegration [11]. Many studies have reported on the use of 3D finite element analysis (FEA) in mandibular reconstruction [12][13][14][15][16]. However, most of these studies deal with a postoperative analysis.…”
Section: Introductionmentioning
confidence: 99%